Deescalating distrust: a deliberative approach to communicating with right-wing populists and supporters - Jakobsen, Jonas (Frontiers in Political Science, 2025)
The paper explores the relationship between deliberative democracy and right-wing populism by focusing on the issue of (dis)trust in political communication. Should we trust right-wing populists enough to include them in political deliberation and, if so, how? The first part outlines a deliberative approach to political communication under conditions of political distrust. In a second step, I argue that theorists such as Habermas and Rummens contradict their own commitment to deliberative democracy by taking a militantly (or semi militantly, in the case of Habermas) democratic approach according to which right-wing populists should be excluded from democratic politics - or even banned. This approach, I argue, is more likely to escalate than de-escalate the spiral of distrust between populist and non-populist parties and citizens. It also runs counter to the deliberative ideal of political justification understood as a discursive process in which all arguments are heard and all affected persons (or their representatives) included. The rest of the article discusses the more delicate question of how to communicate with right-wing populists and supporters, and, especially, how to maintain a balance between justified and unjustified distrust. Given the communicative conditions and pathologies of the mediatized public sphere, I argue, opponents of right-wing populism are forced to use deliberative rhetoric and deliberative contestation as alternatives to deliberation proper (that is, face-to-face discussion, listening and argumentation). In addition, I argue in favor of deliberative outreach towards right-wing populist and even extreme groups, aiming to find a common ground when possible.